High intensity pulsed ion beam sources and their industrial applications; Surface and Coatings Technology; Vol. 114, iss. 2-3 - Remnev (Remnyov) G. E. Gennady Efimovich; Isakov I. F.; Opekounov M. S.; Matvienko V. M.; Ryzhkov V. A. Vladislav Andreevich; Struts V. K.; Grushin I. I.; Zakoutayev A. N.; Potyomkin A. V.; Tarbokov V. A. Vladislav Aleksandrovich; Tarbokov A. N.; Kutuzov V. L.; et al. (1999, 1999)
Title screen